"Depois, é o céu abscôndito do nada" : o niilismo e a poética de Augusto dos Anjos - Ribeiro, Sileyr dos Santos (2016)
This master's dissertation studies both the inherent relations of the nihilist phenomenon fathoming its core mainly under the perspective of Nietzsche’s philosophy and dos Anjos’s poetry with a focus on the utmost renounce of knowledge symptomised by the wearied spirit that engages in the schopenhauerian ascesis to shun of the pain of the ever returning desire. Those attitudes, namely, the renounce and the ascesis are both passive outcomes of the loss fundamental grounding and meaning of the objective world.